Prof. K. Pergelov on the Functions of Financial Accounting and Its Modern Interpretation - Nikolova, Nikolina (Research Papers, 2023)
An important topic in the scientific works of Prof. K. Pergelov is the issue of financial accounting. According to this scholar, accounting is there to fulfill its specific purpose and in a number of publications he goes on to clarify the nature of these functions by making a detailed classification of them and via examining their interrelated manifestations and interdependence. Pergelov defines the informational, analytical and controlling functions of accounting as fundamental and the cognitive (epistemological), prognostic and educational - as their derivatives.Prof. K. Pergelov sees the development and enhancement of the functions of accounting as an objectively conditioned and historically determined social process. Viewed from this angle, and based on the works of K. Pergelov, current day special literature witnesses an ongoing wide and in depth discussion on the functions of financial accounting and its modern, up-to-date interpretation. The article is elaborated to present Prof. K. Pergelov`s fundamental views on the functions of financial accounting and explicates some of the current aspects of their interpretation.
Keywords: The functions; Accounting; Method; Subject; Accountability